DIFFERENT VOICING PATTERNS BETWEEN BRITISH ENGLISH AND KENYAN ENGLISH PLOSIVES (The University of Nairobi Journal of Language and Linguistics, 2023)
This paper is about the VOT characteristics of the six English plosiveconsonants as they are realised in the non-ethnically marked KenyanEnglish pronunciation. This is compared with the General British (GB)1pronunciation. The data analysed in the paper was obtained from readingof the Boy Who Cried Wolf passage by a sample of 14 university lecturers,who served as speakers. Half of the sample was female and the other halfmale. The passage was phonemically transcribed using the Phonetizer*software. The output of transcription was further cross-checked using theOxford Advanced Learner’s Dictionary. The pronunciation of four tokenwords containing the six GB plosives occurring in syllable onset wasanalysed using Praat (a speech analysis software developed by Boersma &Weenink, 2016). Quantitative data on segment duration was analysedusing the Statistical Package for Social Sciences (SPSS). The study foundthat the non-ethnically marked KenE pronunciation, unlike GB, typicallydoes not aspirate voiceless plosives where they are expected to beaspirated, i.e. in initial stressed syllables, while it fully voices their voicedcounterparts.